Stenting for Advanced Esophageal Carcinoma - Kim, Kun Yung; Shin, Ji Hoon; Park, Jung-Hoon (Digestive Disease Interventions, 2018)
Esophageal cancer is the eighth most common malignancy and the sixth leading cause of cancer-related deaths worldwide. Most patients with esophageal cancer are identified at an advanced stage of disease. Less than 20% of patients are candidates for curable surgical resection. Self-expandable metallic stents (SEMSs) have recently been used for the palliation of incurable esophageal cancer. Since their use was first reported in the late 1970s, stents have evolved rapidly from rigid plastic tubes to flexible SEMSs. This review covers various aspects of SEMS placement for advanced esophageal cancer and discusses multiple types of SEMSs, considerations in stent placement, complications, and recently developed radiation-emitting stents.
Keywords: Esophageal Malignancy; stent